Diagnostic Significance of S100 Protein and Phospholipase A2 in Bacterial Injures of CNS in Premature Infants - Lezhenko, G.; Pashkova, O.; Samoylyk, K.; Volotko, L.; Леженко, Геннадій Олександрович; Пашкова, Олена Єгорівна; Самойлик, Катерина Валеріївна (My University, 2020)
The level of S100 and phospholipase A2 were analyzed in the blood serum of 34 newborns with pathology of CNS. Depending on the nature of CNS lesions, two groups of newborns were identified: the study group - 14 premature newborns with bacterial meningitis (mean gestation age is 31,7±0,9 weeks), and the comparison group - 10 premature newborns (mean gestation age is 32,3±0,4 weeks) and 10 fullterm newborns (gestational age is 38,7 ± 0,5 weeks) with severe hypoxic-ischemic injury of CNS. The study of children in the study group was conducted twice: in the acute period of the disease and in the period of convalescence on reaching their postconceptual age of 38-40 weeks. The control group consisted of 18 full-term newborns with a gestational age of 38,6±0,3 weeks without signs of CNS injury and inflammatory diseases. It was found that content of S100 protein in the blood serum of premature newborns has a diagnostic value in relation to assessing the risk of meningitis. With its value equal to 104,1 ng/l or more, meningitis is diagnosed with a sensitivity of 85,7% and a specificity of 75,0%.The determination of this protein in blood serum can also be used as an additional biochemical marker in premature newborns with meningitis to monitor the effectiveness of therapeutic measures. At the same time, increased serum phospholipase A2 activity is not a specific diagnostic marker of meningitis in preterm newborns, but reflects the processes of CNS damage regardless of the etiology of the disease.
Keywords: meningitis; S100 protein; phospholipase A2; premature newborns